1990
DOI: 10.1111/j.1439-0434.1990.tb01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria cassiae Alters Phenylpropanoid Metabolism in Sicklepod (Cassia obtusifolia)

Abstract: Phenylpropanoid metabolism has been implicated in plant defence mechanism(s) against pathogen attack. In this study, phenylpropanoid metabolism was examined over a 72 h time course in the weed sicklepod (Cassia obtusifoiia) in relation to pathogenic effects of the fungus Ahemima cassiae. When 3-to 4-week old seedlings were challenged by the pathogen, extractable phenylaianine ammonia-lyase (PAL, E.C. 4.3.1.5) activity was dramatically increased above that in uninfected plants several hours after inoculation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…The effects of A. cassiae on phenolic metabolism in C. alata were quite similar to those reported for A. cassiae-C. obtusifolia interactions (Hoagland 1990b). Both PAL activity and PAL product (soluble hydroxyphenolic) levels were increased within hours of treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The effects of A. cassiae on phenolic metabolism in C. alata were quite similar to those reported for A. cassiae-C. obtusifolia interactions (Hoagland 1990b). Both PAL activity and PAL product (soluble hydroxyphenolic) levels were increased within hours of treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, investigations concerning the biochemical interactions of Alternaria crassa (Sacc.) Sands and A. cassiae for jimsonweed (Datura stramonium L.) and sicklepod, respectively, hâve shown that phenylalanine ammonia-lyase (PAL) and phenolic products regulated by PAL increase in response to infection (Hoagland 1990b;Hoagland and Boyette 1994). To provide further insight into défense mechanisms of plants challenged by A. cassiae, and due to the importance of pathogen-plant interactions, the following studies were undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…AlCl3 specifically reacts with flavonoids yielding a fluorescing complex (10). A flavonoid structure was assumed based on UV absorbance and fluorescence emission spectra as well as the UV spectral shifts observed upon treatment with AlCl3 (17) and an increase in phenylalanine ammonia lyase (4). We now describe the purification and chemical characterization ofthis compound, a flavonoid possessing a phenoxy group at the 2-position ofthe chromone ring.…”
mentioning
confidence: 99%
“…Furthermore, PAL was suggested as a target site for herbicides [59] and PAL activity was shown to be elevated or inhibited by various herbicides [60]. The fungal pathogen Alternaria cassiae, has bioherbicidal activity against sicklepod (Senna obtusifolia) [61] [62] [63], and alters phenylpropanoid metabolism in this weed [64]. PAL activity levels were increased prior to visual symptoms of pathogenesis when A. cassiae spores were applied to seedlings.…”
Section: Toxicity Tests Of Glufosinate On C Truncatummentioning
confidence: 99%